A framework for an agent-based dynamic pricing for broadband wireless price rate plans. Issue 2 (3rd April 2019) - Elreedy, Dina; Atiya, Amir F.; Fayed, Hatem; Saleh, Mohamed
Abstract: Dynamic pricing is the science of pricing a product in a time-varying way for optimising revenue. There is a slow but steady tendency over the last three decades for major businesses to move from fixed pricing to dynamic pricing. In this paper, we consider the problem of dynamic pricing for wireless broadband data. We propose a novel dynamic pricing approach, based on optimally adjusting premiums and discounts over the prevailing rate, where these adjustments are a function of traffic and demand conditions. Moreover, we propose an agent-based framework for designing and testing this or any other rate plan. In this framework, we have several offered broadband data rate plans, and we model subscribers as agents which react to the dynamic changes of the prices. The proposed framework can be used by wireless operators as a testbed to explore the success of novel dynamic rate plans, and optimise their revenue.